Análise morfométrica e simulação das áreas de preservação permanente de uma bacia hidrográfica - Nardidi, Rafael Calore [UNESP]; Pollo, Ronaldo Alberto [UNESP]; Campos, Sérgio [UNESP]; Barros, Zacarias Xavier de [UNESP]; Cardoso, Lincoln Gehring [UNESP]; Gomes, Luciano Nardini (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2013)
The morphometric characterization of watersheds is of great importance in assisting the planning of these areas to preserve the environment and maintain the quantity and quality of water production. The aim of this study was to characterize the morphology and simulate the areas of permanent preservation according to the Brazilian Forest Code of watershed of the Água-Fria stream. The studied area is located in the municipality of Bofete-SP, between the geographic coordinates: 48° 09' 30" to 48° 18' 30" longitude (WGr) and 22° 58' 30" to 23° 04' 30" latitude S. The results showed a 5th order micro watershed with an area of 152.43 km2 and low drainage density of 1.04 km/km2. Circularity was 0.51 and form factor was 0.41, which is considered low, and therefore with an oblong/oval shape. The sinuosity index of 1.29 revealed a tendency of rectilinear channels with compactness coefficient value of 1.38 and distance of runoff flow of 520m. Simulation of areas of permanent preservation shows an ideal model as the way springs and watercourses should be protected according to the Brazilian Forest Code, amounting to an area of 10.02 km2.

A caracterização morfométrica de bacias hidrográficas é de fundamental importância no auxilio para planejamento dessas áreas com a finalidade de preservação ambiental e manutenção de produção de água em quantidade e qualidade. O presente estudo teve como objetivo caracterizar a morfometria e realizar a simulação das áreas de preservação permanente segundo o Código Florestal Brasileiro da microbacia hidrográfica do Ribeirão Água - Fria. A área estudada localiza-se no município de Bofete-SP, entre as coordenadas geográficas: 48° 09' 30" a 48° 18' 30" de longitude WGr. e 22° 58' 30" a 23° 04' 30" de latitude S. Os resultados apresentaram uma microbacia de 5a ordem com área de 152,43km2, baixa densidade de drenagem de 1,04 km*km-2. Apresentou circularidade de 0,51 e fator de forma de 0,41, considerado baixo, indicando uma forma oblonga/ovalada. O índice de sinuosidade de 1,29 indica tendência a canais retilíneos, com coeficiente de compacidade no valor de 1,38 e distância do escoamento da enxurrada de 520m. A simulação das áreas de preservação permanente mostra um modelo ideal de como deveriam estar protegidas as nascentes e cursos d’água segundo o Código Florestal Brasileiro, totalizando uma área de 10,02 km2.
Morphometric analysis and simulation of permanent preservation areas of a micro watershed
Keywords: Micro watershed; Morphometry; Dimensional parameters; Microbacia hidrográfica; Morfometria; Parâmetros dimensionais